Improving the ablastic capacity of intravitreal chemotherapy for retinoblastoma (Ukrainian Journal of Ophthalmology, 2025)
Background: Intravitreally (IV) administered cytostatics are believed to be a promising local chemotherapy for retinoblastoma (RB) because this approach enables the highest level of chemotherapeutic agent after its direct injection into the ocular cavity. Intravitreal administration is, however, invasive. Among the factors that prevent the wide use of intravitreal chemotherapy (IVitC) for RB is the risk of intraocular complications. In addition, exteriorization of the intraocular tumor may occur through the injection channel or extrabulbar tumor spread may occur.Purpose: To develop a technique of IVitC for intraocular RB to improve its ablastic capacity through the prevention of extrabulbar tumor spread.Material and Methods: An ablastic technique of IVitC was developed at the Department of Pediatric Eye Disorders, the Filatov institute, and used to perform 253 IV injections in 30 children (37 eyes) with T1 to T3 retinoblastoma.Results: The advantages of the newly developed IVitC technique are as follows: achieving ocular hypotony without additional paracentesis; preventing reflux from the vitreous cavity by displacing the conjunctiva above the intravitreal entry point and forming an obliquely perpendicular injection channel; treating the site of scleral puncture with cotton swab tamponade and applying antibiotic solution subconjunctivally;  preventing an infection of the vitreous and scleral thinning in repeat IVitC. There were no perioperative or postoperative complications. In addition, there were no signs of extrabulbar tumor spread during follow-up after IVitC. The number of IV injections per eye ranged from 1 to 13.Conclusion: An improved ablastic capacity of the developed IVitC technique was achieved by reducing (a) reflux from the vitreous through a number of above manipulations and (b) traumatic effect of intervention, as well as preventing complications, which enabled the minimal invasiveness and safety of the technique.
Keywords: retinoblastoma; chemotherapy; intravitreal injection